2016
DOI: 10.1002/prot.25156
|View full text |Cite
|
Sign up to set email alerts
|

Molecular aspects of the interaction between Mason—Pfizer monkey virus matrix protein and artificial phospholipid membrane

Abstract: The Mason-Pfizer monkey virus is a type D retrovirus, which assembles its immature particles in the cytoplasm prior to their transport to the host cell membrane. The association with the membrane is mediated by the N-terminally myristoylated matrix protein. To reveal the role of particular residues which are involved in the capsid-membrane interaction, covalent labelling of arginine, lysine and tyrosine residues of the Mason-Pfizer monkey virus matrix protein bound to artificial liposomes containing 95% of pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 56 publications
0
5
1
Order By: Relevance
“…The lower affinity of the M-PMV MA, a D-type retrovirus, to liposomes has previously been observed by Kroupa et al (41), where only 5% of the M-PMV MA was bound to PI4,5P 2 -containing liposomes in contrast to more than 40% of the HIV-1 MA bound to the same liposomes. In our previous study, we found that ;50% of the M-PMV MA was bound to PI4,5P 2 -containing liposomes (39). However, the concentration of the phospholipids used in the mixture of M-PMV MA and liposomes was almost five times higher than that used by Kroupa et al (41) and twice as high as in our current study to obtain a sufficient amount of protein bound to the liposomes for subsequent mapping experiments.…”
Section: Liposome Binding Of Hiv-1 and Mmtv Mascontrasting
confidence: 58%
See 4 more Smart Citations
“…The lower affinity of the M-PMV MA, a D-type retrovirus, to liposomes has previously been observed by Kroupa et al (41), where only 5% of the M-PMV MA was bound to PI4,5P 2 -containing liposomes in contrast to more than 40% of the HIV-1 MA bound to the same liposomes. In our previous study, we found that ;50% of the M-PMV MA was bound to PI4,5P 2 -containing liposomes (39). However, the concentration of the phospholipids used in the mixture of M-PMV MA and liposomes was almost five times higher than that used by Kroupa et al (41) and twice as high as in our current study to obtain a sufficient amount of protein bound to the liposomes for subsequent mapping experiments.…”
Section: Liposome Binding Of Hiv-1 and Mmtv Mascontrasting
confidence: 58%
“…Additionally, the comparison of HIV-1 and MMTV MA LBA results shows that the HIV-1 MA HBR is able to mediate stronger electrostatic interactions than the HBR of the MMTV MA because HIV-1 exhibits a higher affinity to the liposomes than the MMTV MA under the same experimental conditions. Moreover, the higher affinity of the HIV-1 MA to PI4,5P 2 -containing liposomes as compared with another B/D-type retrovirus, M-PMV, has been observed previously (39,41), although its HBR is located at the N terminus of the MA and comprises eight basic residues. Therefore, we suppose that the affinity of different MAs to PI4,5P 2 is related to the morphogenesis of particular retroviruses.…”
Section: Plasma Membrane Recruitment Of Morphogenetically Different Retrovirusesmentioning
confidence: 66%
See 3 more Smart Citations